Digitalizing Gratitude and Building Trust through Technology in a Post-COVID-19 World—Report of a Case from Japan - Jun-ichi Yamamoto; Tomohiro Fukui; Kazutomo Nishii; Ichiro Kato; Quang Thahn Pham (Journal of Open Innovation: Technology, Market and Complexity, 2022)
Employee engagement has become a critical issue in Japanese companies. One way to develop it is to improve the relationship among employees through gratitude expressions. In the post-COVID-19 remote work environment, digital devices are essential. This paper confirms that expressions of gratitude delivered via digital devices enhance the relationship between employees. We experimented in a small-town government office where participants (n = 88) were asked to (1) use the Thanks App, an app we developed to express gratitude, for two months and (2) respond to an engagement survey we developed before and after the experimental period. Through cross-analysis of the data from the app and questionnaire, we found that the “trust in colleagues” factor had a strong correlation (r = 0.80, p < 0.001) with our new index computed by the app’s data. The results suggest that the use of the Thanks App may help visualize the trust relationship among teams. This study has a practical value in providing a new team management tool for visualizing team trust. In addition, it provides a new research method for emotional and social psychology using digital devices.